Acute Hemodynamic Responses to Enhanced External Counterpulsation in Patients With Coronary Artery Disease - Zhang, Yahui; Chen, Ziqi; Mai, Zhouming; Zhou, Wenjuan; Wang, Hui; Zhang, Xiaodong; Wei, Wenbin; Du, Jianhang; Wu, Guifu (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Enhanced external counterpulsation (EECP) is a noninvasive treatment that increases coronary flow in patients with coronary artery disease (CAD). However, acute responses of vascular and blood flow characteristics in the conduit arteries during and immediately after EECP needs to be verified. Methods: Forty-two patients with CAD and twenty-one healthy controls were recruited into this study to receive 45min-EECP. Both common carotid arteries (CCAs, LC and RC), the right brachial (RB) and right femoral artery (RF) were imaged using Color Doppler ultrasound. Peak systolic velocity (PSV), end-diastolic velocity (EDV), mean inner diameter (ID), resistance index (RI) and mean flow rate (FR) were measured and calculated before, during and after 45min-EECP treatment. Results: During EECP, in the CCAs, ED was significantly decreased, while RI was markedly increased in the two group (both P<0.01). However, immediately after EECP, RI in the RC was significantly lower than that at baseline in patients with CAD (P=0.039). FR of the LC was markedly increased during EECP only in CAD patients (P=0.004). PSV of CAD patients was also significantly reduced during EECP (P=0.015) and immediately after EECP (P=0.005) compared with baseline. Moreover, ID of the LC, RB and RF was significantly higher immediately after EECP than that at baseline (all P<0.05) in patient with CAD. In addition, they were also higher than that in control groups (all P<0.05). Furthermore, by the subgroup analysis, there were significant differences in the FR, PSV and RI between females and males during and immediately after EECP (all P<0.05). Conclusions: EECP creates different responses of vascular and blood flow characteristics in carotid and peripheral arteries, with more significant effects in the both carotid arteries. Additionally, the more beneficial effects in inner diameters, blood flow velocity, resistance index and flow rate after 45min-EECP were showed only in patients with CAD. More importantly, acute improvement of EECP in the flow rate of brachial artery was showed in males, while flow rate and resistance index of carotid arteries changed in females.